LACTOPEROXIDASE SYSTEM UNDER TROPICAL CONDITIONS: USE, ADVANTAGES AND LIMITATIONS IN CONSERVATION OF RAW MILK AND POTENTIAL APPLICATIONS - Ponce, P. (Revista de Salud Animal, 2013)
The existent knowledge about the use of the Lactoperoxidase system (LPs) on the preservation of raw milk confirms its innocuity to human health, which allowed the lifting of the restriction for system to be used for milk products for international dairy market. Under tropic conditions, thiocyanate concentration needed for activating LPs can be reduced to about half of the established in the Codex Alimentarius guidelines, increasing its use security. When the antimicrobial effect of the LPs disappeared, exacerbation of the pathogen microorganisms was not observed, neither an inhibitory effect on the lactofermentant bacteria, in every case in wich milk was previously pasteurized to 850C during 20 minutes. This method maintains the initial quality of raw milk, classified as excellent, during 8 hours without refrigeration and its use should not be associated to poor hygiene quality conditions; although it is preferable to insert it inside an Integral Milk Quality Control Program. The activation of the LPs before pasteurization increases the efficiency of the thermal treatment, eliminating the contamination with coliforms and thermo-resistant bacteria after treatment. The contínuos use in more than 1 200 millions of milk liters, during 15 years confirms the practical utility under Cubans conditions. The knowledge bases and the practical needs exist for an accelerate use of the LPs in the milk preservation and other food products even drugs in the next years.